Accessible and Inclusive City: Can Kingston Jamaica Measure Up? - Morris, Floyd (Disability Studies Quarterly, 2020)
There is a global thrust towards including and integrating persons with disabilities in the mainstream of society. This has intensified since the establishment of the Convention on the Rights of Persons with Disabilities (CRPD) in 2006 and the Sustainable Development Goals (SDGs) in 2015 by the United Nations. One foundational issue addressed in these documents is that of access to public facilities and mobility. In this article, I assessed the situation of the Anglophone Caribbean, using the city of Kingston Jamaica as the point of departure. Kingston is the largest city in the Anglophone Caribbean and acts as a gateway to other destinations in the region. It has a population of approximately 1 million and there is a high concentration of persons with disabilities living in this geographical space.